Identification and biological activity of some new compounds isolated from aerial parts of Polygonum hydropiper (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
New natural compounds, Polygonolic acid (1), Polygonumate (2) and Hydropiperoic acid (3) along with some known compounds were isolated from aerial part of medicinal plant Polygonum hydropiper. The compounds were isolated upon repeat column chromatography, HPTLC, RP-18 reverse phase column of dichloromethane fraction of the crude methyl extract. Their structures were identified by using spectroscopic technique. Structure of Hydropiperoic acid (3) was identified by single crystal X-ray diffraction study. Microbiological activities of these compounds against some of phytopathogenic fungi and bacteria have been investigated in this study.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (3), 204-213